Gambaran Tingkat Depresi, Ansietas, dan Stres Masyarakat di Kecamatan Tabanan Selama Pandemi Covid-19 - Ni Made Sintha Pratiwi (Jurnal Ilmu Keperawatan Jiwa, 2021)
The increasing number of COVID-19 cases and misinformation is confusing and raises public anxiety. People become worried and anxious about the current situation. The pandemic causes psychological changes such as stress, anxiety, and depression. This study aims to determine depression, anxiety, and stress levels in Tabanan District's community during the pandemic. This research was a descriptive-analytic study using quantitative research methods with a cross-sectional research design. The population in this study was the people of Tabanan District. This study uses the DASS-21 questionnaire. The analysis results showed that the respondents are predominantly (73%) have normal conditions in depression. The level of community anxiety was in the normal range (65,8%). The stress level was also in the normal range (70,8%). The condition shows that the dominant community is at the normal level for depression, anxiety, and stress. However,3.8%ven had a severe level of depression, 6% had an extremely severe level of anxiety, and 3.8% had an extremely severe stress level. The number that is not so big must get more attention from the government so that the respondent's condition does not worsen, which can cause harm to themselves and those around them during the COVIC-19 pandemic.